2000
DOI: 10.1046/j.1440-1630.2000.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy in physical medicine and rehabilitation

Abstract: The therapeutic effects of music are being recognized increasingly in the field of rehabilitation medicine. More music therapists are being employed in physical medicine and rehabilitation centres, with the goal of using music therapy services to assist in the physical recovery and health maintenance of clients. In spite of the benefits of physical rehabilitation programs, client participation to their full potential is often not observed. Music encourages participation in exercises and activities. Music can e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 24 publications
0
36
0
5
Order By: Relevance
“…The intervention group also reported a significantly improved quality of life after the 6 week period. It has previously been reported that PD patients sometimes avoid participation in rehabilitation programmes due to lack of motivation or anxiety [24]. Music is known to elicit emotional responses, as moving to music activates endorphin-related brain's pleasure circuits [23], and since the RGRM™ Method offers social interaction, as well as body awareness and joy of movement through the deliberate use of music, it is possible that this method may enhance the motivation to participate also in other rehabilitation programmes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention group also reported a significantly improved quality of life after the 6 week period. It has previously been reported that PD patients sometimes avoid participation in rehabilitation programmes due to lack of motivation or anxiety [24]. Music is known to elicit emotional responses, as moving to music activates endorphin-related brain's pleasure circuits [23], and since the RGRM™ Method offers social interaction, as well as body awareness and joy of movement through the deliberate use of music, it is possible that this method may enhance the motivation to participate also in other rehabilitation programmes.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended amount of training is twice weekly for at least 12 weeks. Many persons with PD avoid participation in rehabilitation therapies due to fear of falling, anxiety, lack of motivation or pain [24]. The RGRM™ Method is considered enjoyable, motivating and engaging and may help in increasing motivation for rehabilitation.…”
Section: Music As Therapy Has Been Used For Many Years As An Alternatmentioning
confidence: 99%
“…Despite the fact that the implemented MT programme was focused on the physical sphere, a greater improvement in the quality of life in aspects of physical functioning was observed in the MT group, because another MT programme was used, which aims to rhythmically stimulate motor functions (Thaut, 1999;Paul & Ramsey, 2000;Hurt & Thaut, 2009;Bukowska, 2012;Bradt et al, 2010). It may be that in the current study the breathing exercises with music were of importance; however, it is more probable that the IG was simply more optimistic in the assessment of their overall functioning than the CG.…”
Section: Discussionmentioning
confidence: 99%
“…The subject literature throughout the world since the 1980s has been describing positive results achieved with MT methods (such as singing popular songs, or group improvisation) in paediatric rehabilitation (Kennelly & Brien-Elliot, 2001), adults in comas or with post-injury amnesia (Aldridge, Gustorff, & Hannich, 1990;Gilbertson, 2005;Tamplin, 2000) as well as speech rate, articulation and intonation problems for persons with neurogenic communication disorders (Cohen & Masse, 1993;Tamplin, 2005). Additionally, rhythmic auditory stimulation effects in physiotherapy and gait training were analysed (Thaut, 1999;Paul & Ramsey, 2000;Hurt & Thaut, 2009;Bukowska, 2012). In Parkinson's disease it has been proven that music-based movement therapy, i.e.…”
Section: Music Therapy and Quality Of Lifementioning
confidence: 99%
“…Recent brain-imaging studies Lahav, Saltzman, and Schlaug 2007) show that humans, given appropriate auditory inputs, seem to be "tuned" to produce corresponding motor outputs. This unique auditorymotor interplay provides the conceptual basis for the use of music therapy, in particular, active music therapy, where a patient is physically involved in producing music rather than simply reacting to or accompanying music (Pacchetti et al 2000;Paul and Ramsey 2000;.…”
mentioning
confidence: 99%